Microwave Absorbing Material of Ba0.95La0.05Fe12-2xZnxTixO19 (x = 0; 0.5; and 1.0) with Broadband Characteristic at X-band Frequency - Yohanes Edi Gunanto; Henni Sitompul; Maya Puspitasari Izaak; Yosep Sarwanto; Wisnu Ari Adi (Journal of Engineering and Technological Sciences, 2022)
In this study, hexaferrite Ba0.95La0.05Fe12-2xZnxTixO19 (x = 0; 0.5; and 1.0) was synthesized and characterized, which can be applied as microwave absorber in the X-band frequency range. It is a potential candidate for a radar absorbing material for microwave absorption, particularly for use in anti-radar paint in the defense sector. Samples were prepared using solid state reaction synthesis with high energy milling. After sintering at the right temperature, the samples were characterized using an X-ray diffractometer (XRD), a scanning electron microscope (SEM), a vibrating-sample magnetometer (VSM) and vector network analysis (VNA). The XRD characterization results indicated that all samples were in phase and had a hexagonal lattice structure with a P63/mmc space group and a crystallite size between 38 and 45 nm. The surface morphology of the characterization results using SEM showed a heterogeneous particle shape with particle sizes ranging from 140 to 200 nm. Substitution of Ti4+ ions for Fe3+ ions by Zn2+ ions resulted in a decrease of the magnetic saturation (Ms), the magnetic remanence, and the sample’s coercivity field. With a sample thickness of 1.5 mm, the VNA results confirmed that the ability to absorb microwaves and bandwidth will increase along with increase of the substitution value x. The reflection loss value was about -13.3 dB at a frequency of around 11 GHz, with a bandwidth of 1.4 GHz for the sample with x = 1.0 composition.